Motif Siswa Memilih Bersekolah di MAN 1 Padang Panjang - Jumiarti Jumiarti; Junaidi Junaidi (Universitas Negeri Padang, 2022)
This research was motivated by the high interest of students in choosing schools at MAN 1 Padang Panjang, especially students from outside the Padang Panjang area. This is evidenced by the number of students from outside the Padang Panjang area which is more than students from the Padang Panjang area itself. In the 2021/2022 academic year, out of a total of 663 students, 547 of them are students from outside the Padang Panjang area. This study aims to analyze the motives of students choosing to study at MAN 1 Padang Panjang. This study uses a qualitative approach with a descriptive type of research. This Study was analyzed using the phenomenological theory of Alfred Schutz. The informant selection technique used purposive sampling with a total of 15 informants. Data collection techniques are observation techniques, in-depth interviews, and documentation studies. Data analysis was carried out using the Miles and Huberman interactive model consisting of data reduction, data presentation, and drawing conclusions. The results of this study indicate that there are several motives that underlie and cause students to choose to study at MAN 1 Padang Panjang which is divided into motives that cause and motives that encourage them to achieve goals. Because the motifs consist of family motifs, interesting and prominent extracurriculars and the existence of a pesantren/Islamic boarding school system. within the framework of the motive consisting of a desire to be independent, deepen religious knowledge and prepare to continue education to a higher level.